Evaluating Location Alternatives for a New Manufacturing Plant using Weighted Sum Model Method - Dikky Suryadi; Warkianto Widjaja; Muchamad Sobri Sungkar; Kraugusteeliana, Kraugusteeliana; Iwan Adhicandra; Sujito, S. (Journal of Applied Science, Engineering, Technology, and Education, 2023)
This study uses the Weighted Sum Model to analyze location possibilities for a new manufacturing plant based on six variables, including transportation cost, labor cost, taxes, utilities cost, closeness to suppliers, and proximity to customers. The data was collected and normalized using the min-max method, and weight values were assigned to each criterion based on their relative importance. The Weighted Sum Model formula was then used to determine the weighted sum for each alternative location, and City B was identified as the best location for the new manufacturing plant, followed by City A and lastly City C. The Weighted Sum Model provides an objective and systematic approach to evaluating location alternatives, allowing decision-makers to weigh the importance of each criterion and consider multiple factors in making informed decisions. The strategy is versatile and can be modified to numerous decision-making scenarios, making it a helpful tool for firms wishing to make location decisions based on data-driven approaches. In conclusion, the Weighted Sum Model is a useful tool for analyzing location possibilities for a new manufacturing plant and can help firms make informed and data-driven decisions regarding the optimum location for their operations